Glycerol mediates crosstalk between metabolism and trafficking through the golgin Imh1 - Chiu, Wan-Yun; Wang, Yi-Hsun; Lin, Ming-Chieh; Lai, Chun-Chi; Yu, Chia-Jung; Lee, Fang-Jen S (Nature structural & molecular biology, 2025)
The golgins are long coiled-coil proteins involved in vesicular transport to the Golgi, a process that contributes to Golgi function and integrity. Previous studies have elucidated that their self-interaction and their interaction with small guanosine triphosphatase Arl1 are critical for their Golgi localization but other mechanisms regulating their localization are not identified. Here we report that glycerol promotes Golgi localization of Imh1, a prototypic yeast golgin. We found that various cellular conditions leading to reduced glycerol level release Imh1 from the Golgi and this release is reversed by restoring the intracellular glycerol level. Elucidating how glycerol regulates Imh1 localization, our results suggest that glycerol acts directly on Imh1 to fine-tune its conformation. Furthermore, we show that glycerol also promotes Golgi localization of a mammalian golgin. Thus, our findings reveal a previously unappreciated connection between intracellular metabolism and transport.